2021
DOI: 10.3390/w13091317
|View full text |Cite
|
Sign up to set email alerts
|

Design, Scaling, and Development of Biofilters with E crassipes for Treatment of Water Contaminated with Cr (VI)

Abstract: The heavy metal water treatment process is the subject of worldwide research. Chromium (VI) is a heavy metal that is very dangerous to humans due to it being able to alter genetic material and cause cancer. Cellulose is an interesting material for removing heavy metals, and excellent removals have been achieved in many experiments at the laboratory scale. However, scaling these processes to polluting industries is not easy. The objective of this research is to design, scale, and test a biofilter with biomass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Previous research has demonstrated the efficacy of E. crassipes biomass in removing Cr (VI) and Pb (II) from continuous systems. For instance, in [1][2][3][4], over one liter of Cr (VI)-contaminated water was treated, resulting in the removal of approximately 80% of the chromium found in tannery wastewater, with around 50 g of this biomass.…”
Section: Results Of Adsorptions Of Cr (Vi) and Pb (Ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated the efficacy of E. crassipes biomass in removing Cr (VI) and Pb (II) from continuous systems. For instance, in [1][2][3][4], over one liter of Cr (VI)-contaminated water was treated, resulting in the removal of approximately 80% of the chromium found in tannery wastewater, with around 50 g of this biomass.…”
Section: Results Of Adsorptions Of Cr (Vi) and Pb (Ii)mentioning
confidence: 99%
“…The model is correlated with the Langmuir isotherm. The Carreño model is used to determine the design parameters of this type of system [1][2][3][4][5], in the Table 1, is the Adsorption models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hydroxyl (OH) and carboxylic (COOH) groups in cellulose leads to the removal of heavy metals by adsorption through cation exchange or chemical mechanisms [17,18]. This cellulose is found in considerable amounts within the aquatic plant E. crassipes [19][20][21][22], which is abundant in tropical environments due to its dry biomass resulting from regular cleaning in the wetlands, lagoons, and rivers of Bogotá D.C. [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical precipitation is the most applied, for the removal of heavy metals. However, this method generates substantial amounts of highly contaminated sludge, and its implementation and operation are very expensive 2 .…”
Section: Introductionmentioning
confidence: 99%